2023
DOI: 10.1088/1748-0221/18/01/p01003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fast neutrons with the pixel detector Timepix3

Abstract: We examined the response of the pixel detector Timepix3 with silicon sensor to well-defined fast neutron fields. Part of the pixel detector silicon sensor was additionally equipped with a neutron mask of distinct converter regions. The mask consists of separate thermal and fast neutron regions using 6LiF and hydrogen (plastic) converters, respectively. Measurements were performed with mono-energetic fast neutrons produced at D-D and D-T sources from a Van de Graaff accelerator and a neutron generator, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…The TPX3 detector, in combination with a suitable converter, can also be used for neutron detection of both D-D and D-T sources. This has been demonstrated in previous research studies [ 9 , 10 ], which have shown its effectiveness in detecting both fast and thermal neutrons.…”
Section: Introductionsupporting
confidence: 67%
“…The TPX3 detector, in combination with a suitable converter, can also be used for neutron detection of both D-D and D-T sources. This has been demonstrated in previous research studies [ 9 , 10 ], which have shown its effectiveness in detecting both fast and thermal neutrons.…”
Section: Introductionsupporting
confidence: 67%
“…The hybrid semiconductor pixel detector Timepix3 [10] is operated at room temperature and is controlled and readout by the compact radiation camera MiniPIX Timepix [11] -figure 1. The Timepix3 ASIC chip bump-bonded to a 500 μm thick silicon sensor was additionally equipped with a neutron mask of segmented distinct regions of thermal converter ( 6 Li ≈ μm thick) and fast converter (segmented plastic polyethylene (PE) of consecutive thicknesses: 50, 100, 150 μm) [12] figure 1c. Integrated power, control and data readout of the radiation camera are enabled via single USB 2.0 connector to standard PC using the integrated cross-platform (Windows, Linux, MacOS) software tool PIXET [13] which provides imaging visualization of registered particle tracks and online display of the detector response.…”
Section: Miniaturized Radiation Camera Minipix-timepix3 With Neutron ...mentioning
confidence: 99%
“…(C) The pixel detector with a segmented mask in contact geometry with distinct regions of thermal ( 6 LiF) and fast (PE) neutron conversion regions [12]. Reproduced from [12]. ©2023 IOP Publishing Ltd and Sissa Medialab.…”
Section: Miniaturized Radiation Camera Minipix-timepix3 With Neutron ...mentioning
confidence: 99%
“…Another high-LET component (classes d and e, see table 1) of small energy or perpendicular direction (namely protons and light ions -from fast neutron interactions [15]) is shown in figure 5.…”
Section: High-let Particles Non-directionalmentioning
confidence: 99%